Kajian dan Pustaka Falsafat Islam di Indonesia - Nanang Tahqiq (ILMU USHULUDDIN, 2014)
Elucidation of this writing deals with the chronicle of Islamic philosophy in Indonesia, either in terms of the first time it emerged, or in terms of its first literature published. Albeit, according to the historical records, the books of Islamic philosophy were already available since 1961, Islamic philosophy was academically and scholarly introduced by Prof. Dr. Harun Nasution (who is called GBHN: Guru Besar Harun Nasution, the Master Harun Nasution), through an institution the so-called IAIN (Islamic State University) Ciputat. However, after such long time the Islamic philosophy has run, its development is not satisfied, since the master and doctoral program are not pioneered. Even the subject of principals of the Islamic philosophy is not yet totally formulated. Its foremost focus is exceedingly towards the Islamic philosophers.